Bio‐inspired Domino oxa‐Michael/Diels–Alder/oxa‐Michael Dimerization of para‐Quinols. Issue 21 (25th April 2018) - Green, Nicholas J.; Connolly, Catherine A.; Rietdijk, Koen P. W.; Nichol, Gary S.; Duarte, Fernanda; Lawrence, Andrew L.
Abstract: A bio‐inspired, pyrrolidine‐mediated, dimerization of para ‐quinols has been developed. It represents one of the most complex, yet general, dimerization reactions ever disclosed, selectively forming four new bonds, four new rings, and eight new contiguous stereogenic centres. The para ‐quinol starting materials are easily handled, bench‐stable compounds, accessed in just one step from aromatic feedstocks. The reaction can be scaled up to give grams of polycyclic material, primed for further elaboration. Abstract : One four all : A bio‐inspired dimerization of para ‐quinols was developed. This highly complex yet general dimerization reaction selectively forms four new bonds, four new rings, and eight new contiguous stereogenic centres. The para ‐quinol starting materials are easily handled, bench‐stable compounds, accessed in just one step from aromatic feedstocks. The reaction can be scaled up to give grams of polycyclic material, primed for further elaboration.